Proteasome inhibitor-induced coronary vasospasm in multiple myeloma: a case report. Issue 7 (30th July 2021) - Mikhail, Philopatir; Rogers, James; Forsyth, Cecily; Ford, Thomas J
Abstract: Background: Coronary vasospasm is an increasingly recognized cause of myocardial infarction or myocardial ischaemia in patients without obstructive coronary artery disease. A thorough medication review may identify drugs or toxins that could trigger coronary vasospasm. This case provides mechanistic insight into the off-target effect of proteasome inhibition leading to coronary vasospasm in a patient referred with chest pain consistent with typical angina. Case summary: A 72-year-old lady presented with anginal chest pain at rest with electrocardiogram evidence of myocardial ischaemia who was referred for invasive coronary angiography. This demonstrated minor coronary disease without an obstructive lesion. Vasoreactivity testing revealed diffuse coronary vasospasm of the left anterior descending artery. Carfilzomib was identified as the trigger for coronary vasospasm. Symptoms resolved without recurrence after appropriate treatment including cessation of the triggering agent. Conclusion: Coronary spasm is a rare but important adverse reaction to proteasome inhibitors. This case supports the clinical utility of invasive coronary vasoreactivity testing in patients with ischaemia with no obstructive coronary artery disease.